Evaluasi Penerapan Whistleblowing System (Wise) Dalam Mencegah Kecurangan (Studi Kasus Pada Kantor Wilayah DJPB Provinsi Jawa Barat) - Sulaeman, Iman; Yusi Sari , Prima (Jurnal IAKP : Jurnal Inovasi Akuntansi Keuangan & Perpajakan, 2025)
This study aims to determine and analyze the application of the Whistleblowing System (WISE) in preventing fraud at the Regional Office of the Directorate General of Treasury of West Java Province based on indicators published by the National Committee on Governance Policy (KNKG) in its book entitled Guidelines for Whistleblowing System (WBS). Whistleblowing System is information submitted by whistleblowers regarding actions that are thought to be, are, or have committed violations by employees. The object of this research is the Regional Office of DJPb West Java Province. This research used a descriptive qualitative approach with data collection methods of interviews, observation, documentation, and literature study. The resource persons in this research consisted of 15 (fifteen) resource persons who came from internal and external of the Regional Office of DJPb of West Java Province. This research was conducted from October 2024 to January 2025. The data analysis technique used in this research is based on the Miles and Huberman model, consisting of data reduction, data presentation, and conclusion drawing. The credibility test used in this research is source triangulation. The results of this study indicate that the implementation of the Whistleblowing System at the Regional Office of DJPb West Java Province is well implemented with 87.5% fulfilling the elements in the Whistleblowing System Guidelines - SPP (Whistleblowing System).